2022
DOI: 10.1155/2022/4096566
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] A Decision Model for Public Economic Environment Monitoring and Management Decision Using Improved Ant Colony Algorithm

Abstract: The quality of economic development is not sufficient, despite the apparent role that public environmental monitoring and management play in the economy’s rapid expansion. Therefore, enhancing the standard of economic growth is of the utmost importance. It is vital to establish innovative management techniques to support social and governmental transformation in order to raise the standard of economic development. Economic development affects public administration’s fundamental duties and goals. The division o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Therefore, it is necessary to define the optimal path according to the requirements of the macro-socioeconomic field. The improved ACO and similar optimization algorithms have improved evaluations of optimal paths and involve provincial (continental) relief corridors [46], public economic environment monitoring and management [56], and heavy-haul railway networks [57], but they are still not applicable for solving the intercountry economic corridor selection problem. In this paper, the heuristic factors are determined by coupling the path nature, the relationship between economies, and the trade distance to determine the priority in path selection according to the realistic needs of economic corridors.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is necessary to define the optimal path according to the requirements of the macro-socioeconomic field. The improved ACO and similar optimization algorithms have improved evaluations of optimal paths and involve provincial (continental) relief corridors [46], public economic environment monitoring and management [56], and heavy-haul railway networks [57], but they are still not applicable for solving the intercountry economic corridor selection problem. In this paper, the heuristic factors are determined by coupling the path nature, the relationship between economies, and the trade distance to determine the priority in path selection according to the realistic needs of economic corridors.…”
Section: Discussionmentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%